Scarcity Mindset Neuro Network Decoding With Reward: A Tree-Based Model and Functional Near-Infrared Spectroscopy Study - Jiang, Xiaowei; Zhou, Chenghao; Ao, Na; Gu, Wenke; Li, Jingyi; Chen, Yanan (Frontiers in Human Neuroscience, 2021)
Resource scarcity imposes challenging demands on the human cognitive system. Insufficient resources cause the scarcity mindset to affect cognitive performance, while reward enhances cognitive function. Here, we examined how reward and scarcity simultaneously contribute to cognitive performance. Experimental manipulation to induce a polar scarcity mindset and reward conditions within participants under fNIRS recording was implemented to explore the mechanism underlying the scarcity mindset and reward in terms of behavior and neurocognition. Participants showed decreased functional connectivity from the DLPFC to the VLPFC with a scarcity mindset, a region often implicated in cognitive control. Moreover, under reward conditions, the brain activation of the maximum total Hb bold signal was mainly located in the Wleft hemisphere (channels 1, 3, and 4, L-VLPFC and channel 6, L-DLPFC), and there was also significant brain activation of the R-DLPFC in the right hemisphere (channel 17). Furthermore, these data indicate the underlying neural changes of the scarcity mentality and demonstrate that brain activities may underlie reward processing. Additionally, the base-tree machine learning model was trained to detect the mechanism of reward function in the PFC. According to SHAP, channel 8 contributed the most important effect, as well as demonstrating a high-level interrelationship with other channels.